Analysis of Planning Strategies for Sustainable Electricity Generation in Kenya from 2015 to 2035. Issue 7 (18th May 2022) - Maina, Alex; Makathimo, Mwenda; Adwek, George; Opiyo, Charles
Abstract: This research entails the simulation of three possible power scenarios for Kenya from 2015 to 2035 using low emissions analysis platform (LEAP). These scenarios represent the unfolding future electricity generation that will fully satisfy the demand while considering the following: energy security, power generation cost, and impacts on the environment. These scenarios are reference scenario (RS), coal scenario (CS), nuclear scenario (NS), and more renewable scenario (MRS). The findings obtained reveals that the most sustainable scenario while comparing the costs was found to be the coal scenario with a net present value (NPV) of 30 052.67 million though it has the highest greenhouse gases (GHGs) emissions. However, the more renewable scenario (MRS) has the least GHGs emissions but is found to be the most expensive scenario to implement with an NPV of 30 733.07 million. Abstract : The paper provides in‐depth analysis of energy demand scenarios, the demand, transformation, emission, and cost analysis conducted using a low emissions analysis platform (LEAP) to determine the best possible scenario suitable for the Kenya energy space. Upon comparison of scenarios, it is realized that the coal scenario is the most favorable, the added plants size is moderate with the maximum plant capacity added being 300 MW.